Student reading associations during post-revolutionary neoabsolutism - Vašík, Miroslav (Retrospektive, 2025)
How did student associations survive under Austria’s harsh post-1848 regime? This article reveals how two student groups in Prague – one Czech, one German – adapted to heavy state control while preserving their educational and cultural goals. Despite censorship, surveillance, and shrinking membership, these associations navigated legal loopholes and shifting policies to maintain a fragile civic presence. Their story challenges the idea that the 1850s were a purely repressive era and highlights how civic life endured even under neoabsolutism.
Keywords: 1848; bralno društvo; Habsburg monarchy; habsburška monarhija; narodni konflikt; national conflict; neoabsolutism; neoabsolutizem; Praga; Prague; reading association; revolucija; revolution; student associations; students; študenti; študentska društva